1971
DOI: 10.1071/bi9711263
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oestradiol-3,17ß Dipropionate on Spermatogenesis and Lysosomal Enzymes in the Rat Tests

Abstract: Daily intramuscular injections (20 f-Lgjday) of oestradiol-3, 17,8 dipropionate in adult male rats depressed body growth and reduced the weight of the testes and seminal vesicles between 4 and 8 days of treatment.The proportion of soluble acid phosphatase (E.C. 3.1.3.2), acid proteinase (E.C. 3.4.4.23), and ,8-glucuronidase (E.C. 3.2.1.31), increased during oestradiol treatment. There was also an increase in the total amount of acid proteinase and ,8.glucuronidase but no significant change in total acid phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1973
1973
2009
2009

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…If acid phosphatase activity is demonstrated histochemically in the testis, using sodium a-naphthyl phosphate as substrate, then it would be expected that acid phosphatase II (Vanha-Perrula 1971d) would be detected, mainly in the interstitial lysosomes (Vanha-Perttula 1971d). However, in other histochemical studies acid phosphatase that will hydrolyse sodium a-naphthyl phosphate has been found mainly in seminiferous tubular epithelium of the rat testis (Elkington and Blackshaw 1971;Elkington et al 1973). According to Vanha-Perttula (1971d) the tubular acid phosphatases (III and IV) do not hydrolyse a-naphthyl phosphate and should not be detected by this technique.…”
Section: Discussionmentioning
confidence: 97%
“…If acid phosphatase activity is demonstrated histochemically in the testis, using sodium a-naphthyl phosphate as substrate, then it would be expected that acid phosphatase II (Vanha-Perrula 1971d) would be detected, mainly in the interstitial lysosomes (Vanha-Perttula 1971d). However, in other histochemical studies acid phosphatase that will hydrolyse sodium a-naphthyl phosphate has been found mainly in seminiferous tubular epithelium of the rat testis (Elkington and Blackshaw 1971;Elkington et al 1973). According to Vanha-Perttula (1971d) the tubular acid phosphatases (III and IV) do not hydrolyse a-naphthyl phosphate and should not be detected by this technique.…”
Section: Discussionmentioning
confidence: 97%
“…The effects of induced regression by various means on testicular acid phosphatase have usually been studied using histochemical methods. Generally an intense acid phosphatasepositive staining has been reported particularly during the initial stages of spermatogenic regression (Baust et al -1967, Elkington andBlackshaw -1971). Such observations have led to the important concept of lysosomal participation in the process of cytolysis (Reddy and Svoboda -1967, Kochar and Harrison -1971, Elkington et al -1967.…”
Section: Introductionmentioning
confidence: 99%
“…It is also known to inhibit the activity of several testicular enzymes (Blackshaw -1970). However, treatment of adult rats with estradiol caused an impairment of spermatogenesis, but no significant change in the total acid phosphatase activity was recorded (Elkington and Blackshaw -1971).…”
Section: Introductionmentioning
confidence: 99%
“…Peak levels of oestrogens at parturition are higher in the cow than in the other two species. (Elkington & Blackshaw, 1971a (Elkington & Blackshaw, 1971b) in which the 'free' enzyme indicates lysosomal fragility and which may be com¬ pared with the total enzyme activity of the preparation.…”
Section: (Queensland 4067mentioning
confidence: 99%